The Impact of Mobile Banking Service Quality Towards Customer Satisfaction Among UTHM Students - SITI NORZIAH ISMAIL,; Nur Nasirah binti Nashir, (Research in Management of Technology and Business, 2023)
Studies on customer satisfaction with the quality of mobile banking services have received attention from researchers. Many studies are conducted to find out the satisfaction of customers from various populations. This study examines the effect of mobile banking service quality on customer satisfaction among Year 4 students at UTHM. This study has two objectives that need to be achieved, the first objective is to investigate the relationship between service quality and customer satisfaction in mobile banking service and second is to determine the level of mobile banking service towards customer satisfaction. This study used a quantitative approach to obtain data by distributing questionnaires to respondents through online. The data obtained was analyzed using SPSS version 26 and the findings of the study were discussed. The findings of this study show that all items in each dimension are reliable. Then, for descriptive analysis, the all items in tangibility and empathy obtain high mean score while one item in each three dimensions which are reliability, responsiveness, and assurance achieve moderate score. This shows that tangibility and empathy have high level towards customer satisfaction then reliability, responsiveness and assurance have moderate level towards customer satisfaction. In addition, dimensions in service quality mobile banking have a positive relationship with customer satisfaction because each dimension has a p- value of less than 0.000 with customer satisfaction. The researcher also suggested some suggestions to overcome the problems faced by the mobile banking service and suggestions for the future in improving future studies. Limitations in this study are also discussed, which are the difficulties faced by the researcher while conducting this study.